Scapular upward rotation position is symmetrical in swimmers without current shoulder pain - McLaine, S. J.; Ginn, K. A.; Fell, J. W.; Bird, M.-L. (Physical Therapy in Sport, 2018)
Objectives: A history of shoulder pain is common in swimmers and may influence scapular position, possibly increasing the risk of shoulder pain recurring. The aim of this study was to establish and compare bilateral static measures of scapular upward rotation in swimmers (14-20 years), some with a history of shoulder pain but all currently pain free, in two different elevated positions of shoulder abduction. Design: Cross-sectional, observational study. Participants: Eighty-five swimmers without current shoulder pain. Methods: Scapular upward rotation position was measured on both shoulders using a digital inclinometer in 90° and 140° shoulder abduction. Descriptive statistics were calculated for degrees of scapular upward rotation in both shoulder positions. Differences between shoulders (dominant, non-dominant, history and no history of pain) were explored using one-way ANOVA and paired t tests. Results: A large range of values for scapular upward rotation was found at both positions of shoulder abduction but there were no significant differences between the shoulders: with and without a history of shoulder pain for the dominant and non-dominant sides. Conclusions: A history of shoulder pain and arm dominance did not influence scapular upward rotation position when measured in shoulder abduction in swimmers without current shoulder pain.